Influence of the mesh size on plastic CTOD - Sanchez-Mancera, J.; Camas-Peña, Daniel; Prates, P.A.; Antunes, Fernando Ventura (ICSI2021 book of abstracts: PMGP Moreira and PJS Tavares, 2021)
The Crack Tip Opening Displacement (CTOD) is an elastic-plastic fracture mechanics parameter usually employed as a measurement of fracture toughness and to explain the fatigue crack growth. This parameter can be decomposed on two different components: the elastic and plastic one. The plastic component is responsible for the degradation of the material while the elastic component is only affecting to the atomic spacing. Lately, the plastic CTOD rage has been considered to study fatigue crack propagation instead of the classical ΔK elastic parameter. In this study, the influence of the mesh size on plastic CTOD results is analysed. For this purpose, a titanium CT specimen is modelled bi-dimensionally using the finite element method. Plane stress conditions are considered. Results are analysed at different places near the crack tip.
Keywords: Materiales - Fatiga; Crack tip opening displacement; Finite element method; Fatigue crack growth